Reliability and Validity of the Composite Activity-Related Fall Risk Scale - Jiang, Yan N.; Wang, Jing X.; Chen, Lin Y.; Yao, Jia J.; Ni, Ling; Sheng, Jie M.; Shen, Xia (Frontiers in Neurology, 2022)
Introduction The newly developed Composite Activity-related Risk of Falls Scale (CARFS) is designed to measure composite activity-related risk of falls (CARF) in relation to the activity-specific fear of falling and physical behavior. This study tested the reliability and validity of the CARFS in older people with various health statuses and persons with stroke or spinal cord injury. Methods Participants included 70 older adults, 38 persons with stroke, and 18 with spinal cord injury. They were first surveyed using a combined questionnaire including the CARFS and activity-specific balance confidence (ABC) scale in addition to items asking for personal and disease-related information, fall history, walking independence levels for examining internal consistency, ceiling and floor effects, and convergent validity in each participant group. One week after the initial survey, 33 older participants were reexamined using the CARFS to analyze test-retest reliability, where a minimal detectable change was found. Significance was set at α = 0.05 for all analyses. Results The CARFS showed excellent test-retest reliability in the dimensions of fear of falling, physical behavior, and CARF [ICC (3,1) = 0.972, 0.994, and 0.994, respectively for their overall score], with a minimal detectable change of 3.944 in the older population. The internal consistency of CARFS items was excellent in the older participants, good in participants with stroke or spinal cord injury (Cronbach's alpha = 0.945, 0.843, 0.831 in each participant group, respectively). No ceiling and floor effects were demonstrated in the wide range of people. For the convergent validity, overall CARF score was significantly correlated with the average ABC score in each participant group (rho = −0.824, −0.761, and −0.601, respectively; p < 0.01), and was significantly correlated with walking independence levels in each participant group (rho = −0.636, −0.423, and −0.522, respectively; p < 0.01). It showed weak correlation with the number of previous falls only in participants with stroke (rho = 0.291, p = 0.076). Conclusion The CARFS is a reliable and valid tool for measuring fall risk in older people and persons with stroke or spinal cord injury.